2021
DOI: 10.4103/ijo.ijo_2649_20
|View full text |Cite
|
Sign up to set email alerts
|

Drug reservoir function of voriconazole impregnated human amniotic membrane: An in vitro study

Abstract: Purpose: Earlier our group has demonstrated the drug reservoir function of the human amniotic membrane (HAM) using stable moxifloxacin and fortified cefazolin ophthalmic formulations and found it as a suitable tool to deliver drugs for an extended duration. The purpose of this study was to evaluate the extended-release kinetics of voriconazole from the impregnated human amniotic membrane (HAM) in vitro . Methods: HAM buttons were incubated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In an in vitro research study, sustained release of voriconazole was observed for up to 5 weeks when voriconazole was incubated with hAM. This provides strong evidence that voriconazole‐impregnated hAM may be considered as a tool for sustained delivery in fungal keratitis 107 . These discussions help provide clues to the role of hAM as a sustained‐release drug delivery system for wound healing.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In an in vitro research study, sustained release of voriconazole was observed for up to 5 weeks when voriconazole was incubated with hAM. This provides strong evidence that voriconazole‐impregnated hAM may be considered as a tool for sustained delivery in fungal keratitis 107 . These discussions help provide clues to the role of hAM as a sustained‐release drug delivery system for wound healing.…”
Section: Discussionmentioning
confidence: 78%
“…This provides strong evidence that voriconazole‐impregnated hAM may be considered as a tool for sustained delivery in fungal keratitis. 107 These discussions help provide clues to the role of hAM as a sustained‐release drug delivery system for wound healing.…”
Section: Discussionmentioning
confidence: 99%